Validity theory: Reform policies, accountability testing, and consequences. (October 2016) - Chalhoub-Deville, Micheline
Educational policies such as Race to the Top in the USA affirm a central role for testing systems in government-driven reform efforts. Such reform policies are often referred to as the global education reform movement (GERM). Changes observed with the GERM style of testing demand socially engaged validity theories that include consequential research. The article revisits the Standards and Kane's interpretive argument (IA) and argues that the role envisioned for consequences remains impoverished. Guided by theory of action, the article presents a validity framework, which targets policy-driven assessments and incorporates a social role for consequences. The framework proposes a coherent system that makes explicit the interconnections among policy ambitions, testing functions, and the levels/sectors that are affected. The article calls for integrating consequences into technical quality documentation, demands a more realistic delineation of stakeholders and their roles, and compels engagement in policy research.